Approaches to the study of intellectual capital based on value-based management - H.M. Tarasiuk; O.P. Pashchenko; I.V. Orlov; N.P. Ignatova (Економіка, управління та адміністрування)
A clear projection of intellectual capital management in order to increase value in the concept of value-based management updates the research in this area. The question of approaches to structuring the intellectual capital of the enterprise is investigated. It is established that the information base for value-based management of intellectual capital is the reporting of enterprises, or rather information about the intangible assets of the enterprise. It is specified that according to the division of intellectual capital into human, structural and customer, not all of the presented components are reflected in the reporting data. It is substantiated that the reporting information can be presented with the help of both financial and non-financial indicators, so it is necessary to analyze both financial and non-financial reporting, which can clarify the specifics of intellectual capital and its components. Four approaches to the study of intellectual capital based on the concept of value-based management are identified, namely: 1) value-based management of intellectual capital; 2) assessment (determination) of the value of intellectual capital; 3) management of the value of intellectual capital; 4) intellectual capital as a driver of enterprise value. It is suggested to choose the issues of value-based management of human, structural and customer capital as components of intellectual capital for further research.